Kebijakan Pendidikan : Dampak Kebijakan Perubahan Kurikulum Pendidikan Bagi Guru Dan Peserta Didik - Anis Aprianti; Siti Tiara Maulia (Jurnal Pendidikan dan Sastra Inggris, 2023)
Education always develops along with the times. Thus there are changes in curriculum policies that are always changing according to the times. Curriculum is the essence of the learning process in an educational institution. With changes to the curriculum, a process is needed that involves the entire community in an educational institution. Indonesia has experienced several curriculum changes, including the curriculum in 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006, 2013 and the independent curriculum. Future education needs to be designed to answer the expectations and challenges of changes that occur. The education system needs to be built continuously from preschool education, basic education, secondary education and higher education. The method used in this study is literature study, namely research that uses material sourced from journals related to education, especially in the curriculum